Metabolic syndrome and chronic heart failure: a modern aspect of the problem (Bangladesh Journal of Medical Science, 2022)
Objective: The increase of morbidity results from both an increase of life expectancy of the population, and influence of various risk factors contributing to development and increase of chronic heart failure (CHF). The combination of several atherogenic mechanisms (abdominal obesity (AO), insulin resistance (IR), arterial hypertension (AH), hyperglycemia, dyslipidemia), combined as “metabolic syndrome” (MS), causes a more rapid development of CHF.Materials and methods: The research finding of 74 patients with class II-III of CHF, including 37 patients (50%) with MS, are presented. The age structure of the pathology, severity of clinical course, data of laboratory and instrumental examination in various groups of patients were evaluated. A special program included an echocardiographic test with an assessment of various myocardial parameters.Results and Discussion: Research materials find out a number of characteristics of CHF clinical course (its earlier development and severe course) in patients with MS. Echocardiographic tests reveal an increase of heart chambers sizes, thickness of left and right ventricle, pulmonary hypertension. Myocardium morpho-functional changes are more significant in patients with CHF and MS than in those without MS. An increase in leptin levels, a marker of obesity, fibrosis and inflammation, has been found. Leptin, C-reactive peptide (CRP) and high-sensitive troponin in patients with MS significantly exceeded those in patientswithout MS. Correlations of leptin levels, adiponectin, CRP and left ventricular mass, thickness of epicardial fat (TEF), ejection fraction were established.Conclusion: Materials of the research indicate the important role of inflammatory and dysmetabolic processes in development and progression of CHF in patients with MS.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 105-113